Implementation of Digital Taxes: Implications for Financial Management in Multinational Companies - Rumasukun, Mohammad Ridwan; Noch, Muhammad Yamin (Manunggal Halim Jaya, 2024)
This qualitative research explores the implications of digital taxation on the financial management practices of multinational companies (MNCs). Employing a systematic review methodology, the study aims to elucidate the impact of digital taxation regimes on MNCs' transfer pricing strategies, profit repatriation decisions, and compliance costs. By analyzing a diverse range of literature from academic databases and reputable sources, the research identifies key themes and insights relevant to the evolving landscape of digital taxation. Findings reveal that digital taxation has prompted MNCs to adapt their transfer pricing methodologies to reflect the value generated by digital activities, ensuring compliance with tax regulations and minimizing tax risks. Moreover, digital taxation influences MNCs' profit repatriation strategies, as they seek to optimize after-tax returns while navigating the complexities of global tax regimes. The study highlights the challenges posed by compliance costs and regulatory uncertainty in the digital taxation landscape, underscoring the need for adaptive strategies and technological solutions to enhance MNCs' financial resilience. Theoretical implications suggest the importance of further research to deepen our understanding of the mechanisms through which digital taxation affects MNCs' financial management practices. Longitudinal studies and comparative analyses across jurisdictions are recommended to inform policy development and managerial decision-making in the dynamic realm of digital taxation. This research contributes to the academic discourse on digital taxation and provides practical insights for MNCs seeking to navigate the complexities of the digital economy.